Інтелектуальна система автоматизації аналізу та опрацювання метрик програмного забезпечення - Говорущенко, Т. О. (Видавництво Львівської політехніки, 2011)
Research is dedicated to developing of intelligent automation system of software metrics analysis and processing (IASMAP) on the basis of neuronet method of evaluation and prediction of software quality (NMEP). IASMAP analyzes and handles the design stage metrics and concludes the complexity and quality of the project and developed software.
Keywords: програмне забезпечення; методологія Safety Case; метрики програмного забезпечення; штучна нейронна мережа